How do we conquer the growth limits of capitalism? Schumpeterian Dynamics of Open Innovation - JinHyo Joseph Yun (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
The purpose of this study is to answer the research question, "How do we conquer the growth limits of capitalism?" Based on existing studies on growth limits of capitalism by Marx and Schumpeter as well as the recent discussions of Drucker, Rifkin, and Piketty, the dynamic model of an open innovation economy system (OIES) is proposed as an answer to this research question. OIES consists of an open innovation economy, closed innovation economy, and social innovation economy. The dynamics of OIES occurs from the positive interaction among the open innovation economy, closed innovation economy, and social innovation economy. The dynamics of the OIES circle are from an open innovation economy, through a closed innovation economy and social innovation economy, and back to an open innovation economy again. In addition, the validation of the model for the dynamics of OIES is improved by simulating the life cycle of the dynamics of OIES, low-level OIES dynamics, and high-level OIES dynamics, and by inquiring about a practical economic system corresponding to each simulation situation. Next through a comparative discussion between the linear steps of Schumpeter 1 and 2, and Socialist Democracy, and the dynamics of an open Innovation economic system, the practical and theoretical characteristics of the dynamics of OIES are clearly defined. Finally, the limits of this study and a follow-up research project are presented in addition to a summary of the discussion.
Keywords: 650; Open innovation economy system; Dynamics; Open innovation; Closed innovation; Social innovation